A Case of Erosive Antral Gastritis Treated with Homeopathy - Maiti, Bishnu Prasad; Khadim, Azizul Islam; Chakma, Abhijit (Homœopathic Links, 2025)
Gastritis is a common gastrointestinal (GI) disorder, which commonly affects children and adult age groups. Antral gastritis is the inflammation of the inner mucosal lining in the antral part of the stomach. It can have a negative impact on health and hinder the quality of life. For the treatment of gastritis, the target should be to prevent recurrence, lessen side effects, and reduce the cost of medications. Considering these aspects, homeopathy can be one of the useful, safer therapeutic options in the treatment of gastritis. A male patient aged 31 years came with complaints of abdominal pain, nausea, vomiting, and distension of the abdomen for the last 10 months. Upper GI tract endoscopy confirmed erosive antral gastritis. He was treated with individualized homeopathic medicine Carbo vegetabilis in LM potency from 0/1 to 0/7. The patient was treated for 9 months with significant improvement both clinically and changes in diagnostic parameters. Endoscopy report revealed a normal study after 9 months of homeopathic treatment. The response of the visual analog scale for pain from +8 to 0 suggests the improvement of patient. In addition, the high score (+8) of Modified Naranjo Criteria for Homeopathy suggested that the likelihood of improvement was attributable to the homeopathic intervention. This case report suggests that a correctly chosen homeopathic medicine can be beneficial in the management of antral gastritis. Nevertheless, more extensive studies are warranted with enhanced methodology.
Keywords: antral gastritis; Carbo vegetabilis; homeopathy; individualization; LM potency